ANALISIS BANGKITAN PERJALANAN PENGARUH PEMBANGUNAN PASAR CITRA MAS LOK TUAN DI KOTA BONTANG - PUTRA, DHIKA (KURVA S JURNAL MAHASISWA, 2014)
Bontang as a city that is growing, should have such facilities. By 2015, the Government of Bontang has begun to build a shopping facility named Mr. Market Citra Mas Lok. With the shopping facilities in the region will affect the activity of the existing road network that is the trip generation that leads around this shopping area. The intent of this study was to determine and analyze the trip generation due to the influence of Mr Lok Market development in Bontang Market development influence Citra Mas Lok Master in Bontang, it can be summed up as follows:Predicted population growth rate of 6% and a growth rate of motor vehicles by 8.3% per year in Bontang.The ratio v / c for road and intersection conditions are 5 yearsRecapitulation predictive ability of the intersection is not signalized Jalan Slamet Riyadi (East and West) - Roads Ships Pinisi 7 at 5 (five) years to come on the performance of the junction in 2020 to do repairs or traffic engineering because of the degree of saturation ratio v / c = 0.833> 0.85 with the level of service close to a D, where the flow is stable, the speed is controlled by the flow of traffic, the driver is restricted in choosing speed.Recapitulation predictive ability of Jalan Slamet Riyadi (East and West) to 5 (five) years to come on the performance of the junction in 2020 obtained the degree of saturation ratio v / c for the East = 0.283 <0.85 and to the west = 0.273 <0.85, with a sense of the level of service at level B, where the flow of cars, the speed is slightly limited by the flow of traffic, the driver can obtain the desired speed.3, Estimated 2015 trip generation and the next 5 years by analogy with the method ITE (Institute of Transportation Engineers) obtained;Trip generation in 2015 sebessar = 399 vehicles / hourPrediction Markets trip generation number Citra Mas Lok Tuan At peak hours during the next 5 years at = 231 smp / hour